“Not the story you want, I’m sure”: Mental health recovery and the narratives of people from marginalised communities - Llewellyn-Beardsley, Joy (2023)
Background: The dominant narrative in mental health policy and practice has shifted in the 21st century from one of chronic ill health or incurability to an orientation towards recovery. A recovery-based approach is now the most frequently used in services in the Global North, and its relevance has also been explored in Global South settings. Despite the ubiquity of the recovery approach, people experiencing poverty, homelessness, intersecting oppressions (based for example on race, ethnicity, gender, sexuality or ability), and other forms of social marginalisation remain under-represented within recovery-oriented research. More inclusive research has been called for to ensure that knowledge of recovery processes is not based solely on the experiences of the relatively well-resourced.